2021
DOI: 10.1021/acs.langmuir.1c01271
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive Core–Shell Fe3O4@poly(N-isopropylacrylamide) Nanogels for Enhanced Oil Recovery

Abstract: An investigation on the application of thermosensitive core−shell Fe 3 O 4 @PNIPAM nanogels in enhanced oil recovery was successfully performed. Here, the unique core−shell architecture was fabricated by conducting the polymerization at the surface of 3-butenoic acid-functionalized Fe 3 O 4 nanoparticles and characterized using X-ray diffraction (XRD), 1 H NMR, vibration sample magnetometer (VSM), and high-resolution transmission electron microscopy (HR-TEM). According to the results, this core−shell structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…35 The complexation between iron oxide and oleic acid can be proven from the appearance of characteristic symmetric ( ν vs ) and asymmetric ( ν as ) of COO − stretches by FTIR analysis. 36 Zhang et al proposed the complex interactions between carboxylate head (COO − ) and Fe atoms in iron oxides could easily be determined by simply calculating the wave number separation (Δ ν ) between ν vs and ν as of COO − , where Δ ν < 110 cm −1 for chelating bidentate, Δ ν = 140–190 cm −1 for bridging bidentate, and Δ ν = 200–300 cm −1 for monodentate interaction. 37 Based on the FTIR results, the calculated Δ ν for Fe 3 O 4 –OA NPs were found to be 97 cm −1 , which revealed that the coordination mode between oleic acid and Fe atoms in Fe 3 O 4 NPs could be classified as chelating bidentate.…”
Section: Resultsmentioning
confidence: 99%
“…35 The complexation between iron oxide and oleic acid can be proven from the appearance of characteristic symmetric ( ν vs ) and asymmetric ( ν as ) of COO − stretches by FTIR analysis. 36 Zhang et al proposed the complex interactions between carboxylate head (COO − ) and Fe atoms in iron oxides could easily be determined by simply calculating the wave number separation (Δ ν ) between ν vs and ν as of COO − , where Δ ν < 110 cm −1 for chelating bidentate, Δ ν = 140–190 cm −1 for bridging bidentate, and Δ ν = 200–300 cm −1 for monodentate interaction. 37 Based on the FTIR results, the calculated Δ ν for Fe 3 O 4 –OA NPs were found to be 97 cm −1 , which revealed that the coordination mode between oleic acid and Fe atoms in Fe 3 O 4 NPs could be classified as chelating bidentate.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic core possesses magnetic field-responsive characteristics, make it possible for microspheres to achieve precise directional movement and aggregation within porous media, reduce oil adhesion to rock surfaces, address the low sweep efficiency caused by heterogeneity, and thus improve oil recovery rates. Khalil et al [17] utilized magnetically responsive Fe3O4 as the core and temperature-responsive PNIPAM as the shell to prepare Fe 3 O 4 @PNIPAM microspheres via reverse-phase microemulsion polymerization. These microspheres exhibited superparamagnetism, allowing rapid recovery and reuse from produced fluid in the presence of a magnetic field.…”
Section: Intelligent Polymer Microspheresmentioning
confidence: 99%
“…However, among these potential nanoparticles, Fe 3 O 4 nanoparticles have garnered significant interest and are extensively utilized in biomedical and pharmaceutical fields. 104,105 These characteristics contribute to the popularity of superparamagnetic iron oxide nanoparticles (SPIONs), which possess excellent biocompatibility, a high capacity for magnetization, and are relatively easy to prepare and functionalize. They have extensive usage across multiple domains such as magnetic resonance imaging (MRI), blood purification, drug administration, magnetic hyperthermia, in vivo biomarker identification, and cell patterning.…”
Section: Magnetic-responsive Polysaccharide Nanohydrogelmentioning
confidence: 99%